Impact of Ocean Warming on Tropical Cyclone Size and Its Destructiveness - Yuan Sun (Nature Portfolio, 2017)
Abstract The response of tropical cyclone (TC) destructive potential to global warming is an open issue. A number of previous studies have ignored the effect of TC size change in the context of global warming, which resulted in a significant underestimation of the TC destructive potential. The lack of reliable and consistent historical data on TC size limits the confident estimation of the linkage between the observed trend in TC size and that in sea surface temperature (SST) under the background of global climate warming. A regional atmospheric model is used in the present study to investigate the response of TC size and TC destructive potential to increases in SST. The results show that a large-scale ocean warming can lead to not only TC intensification but also TC expansion. The TC size increase in response to the ocean warming is possibly attributed to the increase in atmospheric convective instability in the TC outer region below the middle troposphere, which facilitates the local development of grid-scale ascending motion, low-level convergence and the acceleration of tangential winds. The numerical results indicate that TCs will become stronger, larger, and unexpectedly more destructive under global warming.